Trends in stroke mortality in Greater London and south east England--evidence for a cohort effect? - Maheswaran, R (1997)
OBJECTIVE AND SETTING: To examine time trends in stroke mortality in Greater London compared with the surrounding South East Region of England. DESIGN: Age-cohort analysis based on routine mortality data. SUBJECTS: Resident population aged 45 years or more. MAIN OUTCOME MEASURE: Age specific stroke mortality rates, 1951-92. MAIN RESULTS: In 1951, stroke mortality was lower in Greater London than the surrounding South East Region in all age bands over 45. It has been declining in both areas but the rate of decline has been significantly slower in Greater London (p < 0.0001). The differences in rates of decline were such that stroke mortality is now higher in Greater London for people under 75. The crossover of age specific stroke mortality rates occurred at different periods in different age bands and is consistent with a cohort effect, with similar rates in Greater London and the surrounding south east for men and women born around 1916-21. This cohort effect does not appear to be consistent with past maternal and neonatal mortality rates in these areas, nor, within the limitations of the data, with the ethnic composition of cohorts. CONCLUSIONS: There seems to be a cohort effect on stroke mortality which is not explained by past maternal and neonatal mortality. If the decline in stroke mortality continues at its current rate, the Health of the Nation stroke target is unlikely to be achieved in Greater London.